2023
DOI: 10.1017/s0033291723002532
|View full text |Cite
|
Sign up to set email alerts
|

Trauma-focused therapy in early psychosis: results of a feasibility randomized controlled trial of EMDR for psychosis (EMDRp) in early intervention settings

Filippo Varese,
William Sellwood,
Daniel Pulford
et al.

Abstract: Background Trauma is prevalent amongst early psychosis patients and associated with adverse outcomes. Past trials of trauma-focused therapy have focused on chronic patients with psychosis/schizophrenia and comorbid Post-Traumatic Stress Disorder (PTSD). We aimed to determine the feasibility of a large-scale randomized controlled trial (RCT) of an Eye Movement Desensitization and Reprocessing for psychosis (EMDRp) intervention for early psychosis service users. Methods A single-blind RCT … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 49 publications
0
1
0
Order By: Relevance
“…112 A recent feasibility, randomised controlled trial also identified eye movement desensitisation and reprocessing for psychosis as a feasible and promising approach for adults with experiences of developmental trauma in early intervention in psychosis settings, including for those who do not have a PTSD diagnosis. 113 Overall, although initial findings are promising, research of high methodological rigor is needed to explore the potential differential response to current and new evidence-based treatments in this population. 18 In addition, future work could explore whether there are differential responses to treatment in patients with PTSD with psychosis versus developmental trauma survivors who experience psychosis without PTSD.…”
Section: Suggestions For Future Researchmentioning
confidence: 99%
“…112 A recent feasibility, randomised controlled trial also identified eye movement desensitisation and reprocessing for psychosis as a feasible and promising approach for adults with experiences of developmental trauma in early intervention in psychosis settings, including for those who do not have a PTSD diagnosis. 113 Overall, although initial findings are promising, research of high methodological rigor is needed to explore the potential differential response to current and new evidence-based treatments in this population. 18 In addition, future work could explore whether there are differential responses to treatment in patients with PTSD with psychosis versus developmental trauma survivors who experience psychosis without PTSD.…”
Section: Suggestions For Future Researchmentioning
confidence: 99%